2016
DOI: 10.1016/j.joen.2016.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling and Molecular Signaling of Various Cells in Response to Tricalcium Silicate Cements: A Systematic Review

Abstract: TSCs are capable of eliciting a favorable cellular response in periapical regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 81 publications
2
23
0
3
Order By: Relevance
“…The manufacturer states that setting time of Biodentine ® is 12 min and final restoration may be completed in the same appointment [21] . Biodentine ® was reported to set in a shorter time than MTA, as its liquid contains calcium chloride and its powder contains calcium Jang et al [23] reported the setting time of Biodentine ® as 15 min.…”
Section: Biodentinementioning
confidence: 99%
“…The manufacturer states that setting time of Biodentine ® is 12 min and final restoration may be completed in the same appointment [21] . Biodentine ® was reported to set in a shorter time than MTA, as its liquid contains calcium chloride and its powder contains calcium Jang et al [23] reported the setting time of Biodentine ® as 15 min.…”
Section: Biodentinementioning
confidence: 99%
“…Por otra parte, se ha reportado una relación entre procesos de señalización apoptóticos, como la necroptopsia, con la expresión de PARP-1 (Sosna et al). Varios estudios muestran la expresión de citoquinas pro inflamatoria (IL-1β, IL-6, IL-8, NO, PGE2 y TNF-α) en cultivos celulares en presencia de Biodentine, donde han reportado niveles similares en la expresión de TNF-α en CCPDH expuestos a Biodentine y otros CSC (Chang et al, 2014(Chang et al, , 2015Jung et al;Rathinam et al). Resultados similares se han obtenido utilizando cultivos de osteoblastos y odontoblastos (Bortoluzzi et al, 2015;Chang et al, 2015), los que apoyan los resultados obtenidos en este estudio, donde existe mayor expresión de caspasa-3 clivada y PARP-1 a las 48 y 72 horas de exposición a BD.…”
Section: Discussionunclassified
“…La porción sólida contiene silicato tricálcico como agente potencialmente bioactivo (Camilleri et al, 2013), carbonato de calcio y oxido de zirconio como radiopacificador; mientas que el líquido contiene una solución de clorhidrato de calcio, aceleradores y agentes reductores. Este CSC es recomendado como sustitutos dentinarios, en restauraciones coronales, reparación de perforaciones y además como recubridor pulpar, el que luego de aplicado podría estar en contacto directo con la pulpa vital (Rathinam et al, 2016;Emara et al, 2018).…”
Section: Introductionunclassified
“…21 1 3 6 4 2 1 3 2 3 4 Cohesive=203 26 21 20 21 25 24 21 21 22 17 Mix=54 3 6 4 5 3 5 6 7 5 9 effect on microorganisms; therefore, the alkali environment, formed by BD, provides the disinfection of surrounding hard and soft tissues. 22 In a study related to the biocompatibility of BD, Laurent et al 23 reported that, regardless of concentration, BD did not have a cytotoxic or genotoxic effect on pulp fibroblasts; consequently, did not cause modification in the function of these cells when used as a base material or pulp capping agent. About et al 24 reached to the conclusion that BD stimulates dentin regeneration by inducing odontoblast differentiation from pulp progenitor cells in studies examining the activity of BD on activation, differentiation of pulpal progenitor cells and dentin regeneration in human dental cultures.…”
Section: Discussionmentioning
confidence: 99%